2022
DOI: 10.3390/ijms232213713
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Double-Stranded RNA Strategy Improves Cotton Resistance to CBW (Anthonomus grandis)

Abstract: Cotton is the most important crop for fiber production worldwide. However, the cotton boll weevil (CBW) is an insect pest that causes significant economic losses in infested areas. Current control methods are costly, inefficient, and environmentally hazardous. Herein, we generated transgenic cotton lines expressing double-stranded RNA (dsRNA) molecules to trigger RNA interference-mediated gene silencing in CBW. Thus, we targeted three essential genes coding for chitin synthase 2, vitellogenin, and ecdysis-trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…In view of these possibilities, Embrapa Genetic Resources and Biotechnology is developing several scientific research projects aimed at developing transgenic-based technologies capable of 10.3389/fsufs.2023.1296337 Frontiers in Sustainable Food Systems 05 frontiersin.org controlling the CBW. In brief, these new technologies for cotton to control CBW use the expression of Cry toxins or the combination of Cry toxins with RNAi, both of which have already shown promising results in transgenic cotton lines evaluated under greenhouse conditions (Ribeiro et al, 2017(Ribeiro et al, , 2019(Ribeiro et al, , 2022Vasquez et al, 2023).…”
Section: Materials and Methods Of Data Exploredmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of these possibilities, Embrapa Genetic Resources and Biotechnology is developing several scientific research projects aimed at developing transgenic-based technologies capable of 10.3389/fsufs.2023.1296337 Frontiers in Sustainable Food Systems 05 frontiersin.org controlling the CBW. In brief, these new technologies for cotton to control CBW use the expression of Cry toxins or the combination of Cry toxins with RNAi, both of which have already shown promising results in transgenic cotton lines evaluated under greenhouse conditions (Ribeiro et al, 2017(Ribeiro et al, , 2019(Ribeiro et al, , 2022Vasquez et al, 2023).…”
Section: Materials and Methods Of Data Exploredmentioning
confidence: 99%
“…New versions of previously consolidated Cry or VIP3A proteins, as well as new molecules, have recently been released to ensure greater control efficacy and reduce the rate of resistance development of these technologies (Supplementary File S1; ISAAA, 2023). Also, the search for active molecules that have an effect against other insect pest orders is also ongoing, such as molecules for transgenic control of CBW in cotton (Ribeiro et al, 2017(Ribeiro et al, , 2019(Ribeiro et al, , 2022Vasquez et al, 2023). The main crops 10.3389/fsufs.2023.1296337…”
Section: Major Contributions Of Molecular Sciences To Brazilian Agric...mentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of chitin synthase in cotton boll weevils ( Anthonomus grandis ) using RNAi recombinant transgenic cotton resulted in malformed first and third instar larvae. The report suggested that the knockdown of chitin synthase led to the obstruction of nutrient uptake in the gut [ 87 ].…”
Section: Rpw’s Gut Transcriptome Analysismentioning
confidence: 99%
“…Various methodologies can be employed to identify and understand plant cellular mechanisms in response to biotic stress, as well as to develop distinct molecular strategies to reduce negative effects. The studies by Pinheiro et al [4] and Ribeiro et al [5] showed different methods to evaluate plant response to pathogens and limit their deleterious effects. The sterility and resulting susceptibility of bananas (Musa spp.)…”
mentioning
confidence: 99%